Crossing the Rhine breaking into Nazi Germany, 1944 and 1945 : the greatest airborne battles in history - Clark 1967- (Atlantic Monthly Press Distributed by Publishers Group West, 2008)
A British military historian offers an in-depth account of two critical offensives led by Allied troops against the Nazi power base on the Rhine, examining the strategies, military leaders, and campaign of the two airborne assaults, the events leading up to combat, the power struggle among Allied leadership, and the results of the battles on the war?s outcome.